AIDS : an all-about guide for young adults - Silverstein, Alvin; Silverstein, Virginia B.; Nunn, Laura Silverstein (Springfield, NJ : Enslow Publishers, 1999)
An overview of the history, biology, symptoms, diagnosis, treatment, prevention, and future research of AIDS.
Includes bibliographical references and index.
Keywords: AIDS (Disease) -- Juvenile literature; AIDS (Disease); Diseases